Insights into mechanisms of pranoprofen-induced apoptosis and necroptosis in human corneal stromal cells. (1st March 2020) - Lin, Yani; Yu, Miaomiao; Fan, Tingjun
Highlights: In vitro, 0.1 % to 0.00078125 % pranoprofen cause necroptosis and apoptosis in HCS cells. 0.00625 % pranoprofen induces apoptosis through ROS-mediated caspase-dependent and caspase-independent pathways. In vivo, 0.1 % pranoprofen causes apoptosis-like ultrastructural alterations in rabbit corneal stromal cells. Abstract: Pranoprofen (PPF) is a wildly used anti-inflammatory ophthalmic drug. It was reported that PPF could decrease early epithelialization of scrape wounds in rabbit cornea and could reduce cell activities of cultured human corneal endothelial cells. However, effects of PPF on corneal stromal cells playing important roles in corneal wound healing remain unknown. In this study, in vitro model of cultured human corneal stomal (HCS) cells and in vivo model of rabbit corneas were used to investigate the effects and underlying mechanisms of PPF. Our findings showed that high concentrations of PPF treatment (0.1 % to 0.0125 %) caused limited chromatin condensation and quickly decreased cell viability that was proved to initiate necroptosis in HCS cells through activating receptor interacting protein kinase (RIPK) and mixed lineage kinase domain-like (MLKL). While low concentrations of PPF treatment (0.00625 %) induced DNA fragmentation, apoptotic body formation, ROS generation, activation of caspases and increase in cytoplasmic content of Bad, Bax and cytoplasmic cytochrome c that suggested apoptosis happened through ROS-mediated caspase-dependent and caspase-independent pathways. Studies of rabbit corneas treated with 0.1 % PPF (the clinical concentration) showed that PPF could induce apoptosis of rabbit corneal stromal cells. This work would be helpful for better understanding cytotoxic effects PPF on human corneal cells.